2001
DOI: 10.21000/jasmr01010103
|View full text |Cite
|
Sign up to set email alerts
|

Forest Productivity aud Minesoil Development Under A White Pine Plantation Versus Natural Vegetation After 30 Years

Abstract: In 2000, the State of West Virginia passed legislation requiring commercial forest land as a preferred post-mining land use on surface coal mines, and especially on those sites where mountaintop removal mining is occurring and valley fills are being constructed. Due to West Virginia's mountainous terrain, most future surface mine permits will be impacted by this change in post-mining land use. Therefore, interest has been renewed into studies examining forest productivity and minesoil development on areas plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
0
29
1
Order By: Relevance
“…Skousen et al (1994) also reported rapid reforestation of naturally revegetated sites in West Virginia. Our finding that naturally regenerated hardwood stands had a higher basal area than planted pine is contrary to results of Gorman et al (2001) who observed higher forest productivity in planted pine sites in comparison with natural succession after 30 years. However, an assessment of well-stocked forest stands on older coal mine spoils of the eastern and mid-western U.S. showed that planting of pine during reclamation can either increase or decrease forest productivity, depending on the suitability of the pine species to the site (Rodrigue and Burger, 2002), with a maximum productivity of pine at 30-40 years, while hardwood stands matured at 60-80 years.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Skousen et al (1994) also reported rapid reforestation of naturally revegetated sites in West Virginia. Our finding that naturally regenerated hardwood stands had a higher basal area than planted pine is contrary to results of Gorman et al (2001) who observed higher forest productivity in planted pine sites in comparison with natural succession after 30 years. However, an assessment of well-stocked forest stands on older coal mine spoils of the eastern and mid-western U.S. showed that planting of pine during reclamation can either increase or decrease forest productivity, depending on the suitability of the pine species to the site (Rodrigue and Burger, 2002), with a maximum productivity of pine at 30-40 years, while hardwood stands matured at 60-80 years.…”
Section: Discussioncontrasting
confidence: 99%
“…Areas that had been planted with any pine species, and still contained pine, were designated as "pine." On these areas the natural succession of pine to hardwood (Gorman et al, 2001) had been hastened by an outbreak of Southern pine beetle (Dendroctonus frontalis) around 1996, leaving numerous gaps. Therefore plots were selected to minimize the effect of gaps and capture the long-term effects of planted pine.…”
Section: Study Areamentioning
confidence: 99%
“…1-3). This good tree growth was attributed to the random placement of weathered overburden at the surface (overburden selection and placement were not planned or regulated), little or no surface grading to compact the soils, and little or no seeding of grass for revegetation (Ashby, 2006;Gorman et al, 2001). Because the older surface mines were smaller and often disturbed only near-surface rock, weathered overburden materials often comprised the majority of overburden and was placed on the surface loosely, with minimal or no grading.…”
Section: Early Reforestation Of Surface Minesmentioning
confidence: 99%
“…This differential weathering among rock types influences the rate of soil genesis and the future productivity potential of the soil (Gorman et al, 2001;Haering et al, 1993;Johnson and Skousen, 1995;Torbert et al, 1988). Figure 4.…”
Section: Spoils Into Soilsmentioning
confidence: 99%
“…As government regulations progressed, mining companies were required to backfill the area and plant grasses or trees (Gorman et al 2001;Skousen et al 2006). During the ensuing 30 years, more requirements were instituted to promote reclamation and some states had more stringent laws and regulations, and some had a reclamation bond.…”
Section: Laws and Regulationsmentioning
confidence: 99%